Private Activity in Infrastructure Slowed Down in the First Half of 2011, Compared to the Same Period in 2010 - Kaliszewski, Laura (World Bank, Washington, DC, 2014)
In the first half of 2011, 66 energy projects with private participation reached financial or contractual closure in 13 low and middle-income countries. Additionally, US$4.8 billion was invested in the second phase, 1224km expansion of Russia's Nord stream gas pipeline, following the phase one financial closure that occurred in 2010, bringing total investment commitments to the energy sector to US$20.9 billion. Although this activity represents an 18 percent increase by the number of projects, this represents a 24 percent decrease by investment from the similar period in 2010. New investment activity in the sector was concentrated in three countries. India was the most active country, accounting for 21 projects, 42 percent of new investment in the sector and 32 percent of new projects. Brazil, the second most active country, attracted 14 percent of the new investment and 27 percent of new projects, followed by China with 4 percent of new investment and 11 percent of new projects. These three countries accounted for 60 percent of new energy investment and 70 percent of new projects during the first semester of 2011.